Penerapan Platform Pemasaran Digital untuk Meningkatkan Omzet UMKM di Desa Waringin Jaya Bojonggede Kabupaten Bogor - Dwi Uthari Nabilah; Selvi Trasviyati; Abdul Kadir; Nofryanti Nofryanti; Suripto Suripto (Jurnal PKM Manajemen Bisnis, 2026)
The rapid development of digital technology offers significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand market reach and enhance business competitiveness. Nevertheless, MSMEs in rural areas continue to encounter challenges in adopting digital marketing, including limited technological skills, restricted access to information, and low awareness of the importance of digital platforms. To address these issues, a Community Service Activity (PkM) was conducted in Waringin Jaya Village, Bojonggede District, Bogor Regency, from November 14 to 16, 2025. This activity involved 26 participants consisting of MSME actors, village officials, and community members. The program aimed to improve participants’ digital competencies by providing practical knowledge and skills in utilizing digital marketing platforms such as social media, online marketplaces, and websites to promote local products. The implementation method was based on a Participatory Action Approach, positioning MSME actors as active partners throughout the process. The activities included surveys, direct material delivery, simulations, and interactive discussions focusing on target market analysis, basic financial management, and digital product marketing strategies. The results showed an increase in participants’ understanding of digital marketing concepts, their ability to operate digital platforms, and their motivation to integrate technology into their business practices. This activity is expected to support MSME digital transformation, broaden market access, increase sales turnover, and contribute to improving rural economic welfare while reducing the digital divide.